Consumer’s Behaviour in Buying Smartphones in Kathmandu Valley - Humagain, Reem Prasad (Patan Prospective Journal, 2022)
This study related to the factors that affect the mobile purchase decision in Kathmandu valley. Furthermore, the study shows the relationship of demographic factors like gender, age, education level, occupation, income level and marital status with the purchase decision of mobile in Kathmandu valley. Consumers purchase decisions are affected by various factors and it is necessary for any brand to understand the factors that affect the decision. Thus this research is conducted to study factor influencing purchase decision of mobiles in Kathmandu valley. The objective of the research is to identify the influencing factor for the purchase decision of mobiles and to examine the relationship of these influencing factors with the purchase decision of mobiles in Kathmandu valley. Based on the literature review, in the study, the researcher identified variables like, promotional campaign, price, after sales service, mobile attributes, brand name & family and friend influence. The collected data were completely analyzed and interpreted on the objective wise and the major conclusions are given.